Escape and lipodystrophy in acromegaly during pegvisomant therapy, a retrospective multicentre Spanish study. (19th March 2014) - Sesmilo, Gemma; Resmini, Eugenia; Bernabeu, Ignacio; Aller, Javier; Soto, Alfonso; Mora, Mireia; Picó, Antonio; Fajardo, Carmen; Torres, Elena; Álvarez‐Escolá, Cristina; García, Rogelio; Blanco, Concepción; et al.
Summary Background Pegvisomant is an effective treatment for acromegaly. Objective To investigate escape (loss of biochemical control in patients previously controlled) and lipodystrophy in acromegalic patients treated with pegvisomant and to evaluate possible associations with clinical features. Patients and methods Multicentre retrospective study involving 19 Spanish centres. Results Ninety‐seven patients were included (59% women, mean age at diagnosis 42 ± 13 years, 80% macroadenomas); mean follow‐up on pegvisomant was 5 ± 2·5 years, and 89 (92%) achieved normal IGF‐1. Escape was reported in 30/89 (34%) of responders, after a mean treatment duration of 25 ± 21 months. The mean initial dose of pegvisomant was 11 ± 5 mg/day, and mean dose at escape was 14 ± 7 mg/day. Most patients (26/30, 87%) achieved control with dose increase (57%), additional medical treatment (3%) or both (27%). Mean new dose that controlled IGF‐1 after escape was 20 ± 7 mg/day. Treatments associated were somatostatin analogues (SSA in 47%), cabergoline (CAB in 47%) and both (6%). Lipodystrophy was observed in 15 patients (13 females), mild in six, moderate in six, severe in three and persistent in four. Among patients with lipodystrophy, three escaped and three were nonresponders to pegvisomant. Four patients discontinued the drug, and four had dose reductions because of lipodystrophy. It tended to be more frequent in females (P = 0·06) and in patients treated with triple association SSA+CAB+PEG (P = 0·018). No relationship between escape and clinical variables was found, except prior CAB (P = 0·04) and metformin treatment (0·02) and grade of lipodystrophy (P = 0·02). Conclusions A significant proportion of patients treated with pegvisomant escaped (34%); however, the majority (87%) was easily controlled with either dose increase, further medical treatment or both. Lipodystrophy developed in 15%, mostly females, and influenced the response to treatment.